Love Discourse in Octave Mirbeau’s “The Lovers” as Reflected in Translation - Raźny, Joanna (Lustro, 2020)
The aim of the article is to present Octave Mirbeau’s play The Lovers (1904) with regard to the issues of the art of translation. The study is focused entirely on the linguistic and literary methods of how the love discourse is shaped in the play and, within this topic, on the issue of the relationship between feeling and time, the typology of spatial behaviour in the lovers’ interaction, affective nouns, and their role in building intimacy. The theoretical framework is primarily based on literary studies, which include the elements of modern translation study concepts and the achievements of the linguistic research on verbal and non-verbal forms of expressing feelings. The French source text is studied and, with regard to its equivalence, contrasted with its first printed translation — a text in Polish, functioning within the Polish culture and the Polish language. The results of the presented analyses serve, among others, as a justification for the thesis that The Lovers is an intentionally anachronistic play, whose role is to demystify the entanglement of the then-modern conceptualisation about Eros’s affairs with the still romantic patterns and schemas.